Report of a Network Coordinating Group on Sugar, Starch and Fibre Crops: Third meeting, 8-9 October 2009, Quedlinburg, Germany - Frese, L.; Hoekstra, R.; Bioversity International (2009)
Report of the third meeting of the ECPGR Network Coordinating Group on Sugar, Starch and Fibre Crops, 8-9 October 2009, Quedlinburg, Germany